The stories of Vladimir Nabokov - Nabokov, Vladimir Vladimirovič 1899-1977 (A Borzoi book, 1996)
Sixty-five works by Vladimir Nabokov include his fairy tales, puzzles, vignettes, and melancholic stories written between the 1920s and 1950s, and feature such masterpieces as Lolita, Pale Fire, and Ada.